Sorption of Cadmium and Arsenic by Goethite and Clinoptilolite - Dimirkou, A; Ioannou, Z; Golia, E.E; Danalatos, N; Mitsios, I.K (Communications in soil science and plant analysis, 2009)
Cadmium (Cd) and arsenic (As) adsorption and desorption by goethite and clinoptilolite were the subjects of this article. Experimental variables were the concentrations of Cd, As, background electrolyte, and the solution pH. Cadmium adsorption by goethite and clinoptilolite increases with the increase of pH and with the decrease of electrolyte concentration. Maximum Cd desorption by goethite was found at pH 6.0 and by clinoptilolite at pH 8.0 and 0.1 M potassium chloride (KCl). Maximum As desorption by goethite was found at pH 8.0 and by clinoptilolite at pH 10.0 and 0.01 M KCl. The experimental results of Cd adsorption were successfully fitted to Langmuir, Freundlich, and Temkin isotherms, and the experimental results of As adsorption were comparable successfully fitted to Freundlich and Temkin isotherms.